Hear the wolves - Scott, Victoria, (Young adult author) (New York, NY : Scholastic Press, 2017)
Sloan Riley is a skilled hunter, but since her mother left, and she lost hearing in one ear, she has clung to her father and older sister, so waking up and discovering they have left her for a few days terrifies her--but when an autumn blizzard threatens to bury her small Alaskan town, and the wolves begin to hunt, she must find her courage if she is to get herself and the few remaining citizens to safety beyond the forest.
Keywords: Survival -- Juvenile fiction; Self-confidence -- Juvenile fiction; Courage -- Juvenile fiction; Wolves -- Juvenile fiction; Blizzards -- Juvenile fiction; Survival -- Fiction; Self-confidence -- Fiction; Courage -- Fiction; Wolves -- Fiction; Blizzards -- Fiction; Alaska -- Juvenile fiction; Alaska -- Fiction